Modelling and Analyzing the Potential Controls for Neospora caninum Infection in Dairy Cattle Using an Epidemic Approach. (3rd May 2021) - Liu, Yue; Magouras, Ioannis; Lo, Wing-Cheong
Abstract : Neospora caninum ( N. caninum ) infection, one of the major causes of abortions in dairy cattle, has brought a huge loss to farmers worldwide. In this study, we develop a six-compartment susceptible-infected model of N. caninum transmission which is later reduced to a two-equation system. Potential controls including medication, test-and-cull, and vaccination are proposed and analyzed, and the corresponding reproduction numbers are derived. The conditions for the global stabilities of disease-free and endemic equilibria are investigated with analytical solutions and geometric approach. Furthermore, uncertainty and sensitivity analysis shows that three control strategies are effective towards the varied environment, whereas the effectiveness of each measure highly depends on parameters related to control actions. Dynamics of reproduction numbers illustrate that disease elimination can be achieved by three types of controls: (1) adopting medication with medicine efficacy higher than 0.4 to prevent vertical transmission, (2) implementing test-and-cull with culling coverage larger than 0.3, and (3) taking vaccine with coverage larger than 0.1. Numerical results suggest that preventive measures should at least include the prevention of access of other hosts, such as dogs, to cattle; otherwise, these control measures will lose effectiveness. Our presented study provides guidance for decision-making on N. caninum infected farm management.